ANALISIS PSIKOLOGI TERHADAP KONFLIK BATIN TOKOH MUFTI DALAM NOVEL DIKEJAR BAYANGAN KARYA DJAWASTIN HASUGIAN - Fitria Karmila Sari; Yoshinta Aprila Rudyprasasti (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2020)
Literary works are part of works commonly referred to as works of fiction that have links to topics that support life. A writer is free to pour pleasure and live it into fiction. This Beneficial Object uses the novel Chased by Shadow by Djawastin Hasugian. The novel "Chased Shadow" in terms of the psychology of literature. The purpose of this study is to describe the facts of the id, the ego, the superego which are considered the main characters in the novel Chased Shadow. The method in this research is descriptive qualitative. The analysis used in this study uses heuristic and hermeneutic reading methods. Sigmund Freud. The technique of collecting data is reading and taking notes. The results of this study are the Mufti characters in the novel Chased Shadow have aspects of internal conflict that contain Sigmund Freud's theories namely id, ego, superego. Keywords: Inner Conflict, Sigmund Freud, Shadow Chased Novels